2009
DOI: 10.1089/hum.2009.163
|View full text |Cite
|
Sign up to set email alerts
|

The Current State of Head and Neck Cancer Gene Therapy

Abstract: The incidence of head and neck cancer continues to increase worldwide, with tobacco exposure and human papillomavirus type 16 infections being the major etiological factors. Current therapeutic options are ineffective in approximately half of the individuals afflicted with this malignancy. Developments in the identification of molecules that sustain head and neck squamous cell carcinoma (HNSCC) growth and survival have made molecular targeting by gene therapy approaches a feasible therapeutic strategy. Althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 82 publications
1
36
0
4
Order By: Relevance
“…4 Advanced head and neck cancers are the mostly evaluated indications for cancer gene therapy. [5][6][7] To date, there are at least 12 HNSCC gene therapy clinical protocols that have been registered officially in the clinicaltrials.gov registry. 5 Some of these clinical trials produced remarkable tumor remission, with more data coming.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 Advanced head and neck cancers are the mostly evaluated indications for cancer gene therapy. [5][6][7] To date, there are at least 12 HNSCC gene therapy clinical protocols that have been registered officially in the clinicaltrials.gov registry. 5 Some of these clinical trials produced remarkable tumor remission, with more data coming.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7] To date, there are at least 12 HNSCC gene therapy clinical protocols that have been registered officially in the clinicaltrials.gov registry. 5 Some of these clinical trials produced remarkable tumor remission, with more data coming. It cells infected with 20 or 100 MOI of Ad-GFP were GFP positive, which indicated that adenovirus vector was able to infect pancreatic cancer cells efficiently, and adenovirus vector-mediated gene expression could be used for studies on cell biology and animal experiment in pancreatic cancer cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although advances have been made in conventional therapy including surgery, chemotherapy and radiation, their impact on improvement of 5-year mortality rate of patients with HNSCC is still minimal [2]. Increased understanding of molecular events involved in HNSCC initiation and progression has led to the development of gene therapy as a potential treatment option [3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…However, those conventional therapies in particular radiotherapy and chemotherapy, are non-selective and can cause damage to normal tissue. Modification of the approaches have improved cure rate in only approximately half of the patients (Ichwan & Ikeda, 2008;Thomas & Grandis, 2009). Recently, dramatic improvements in our knowledge of the molecular and genetic basis of HNSCC combined with advances in technology have resulted in novel molecular therapies for the disease by targeting of specific molecule in cancer therapy to selectively destroys cancer cells including targeting the function of p53 tumor suppressor.…”
Section: Tumor Suppressor Genes 130mentioning
confidence: 99%